Trends in the levels, causes, and risk factors of maternal mortality in Pakistan: A comparative analysis of national surveys of 2007 and 2019 - Farid Midhet; Samina Naeem Khalid; Shehla Baqai; Shahzad Ali Khan (PLoS ONE, 2025)
Background Maternal mortality ratio (MMR) has decreased worldwide but Pakistan is still striving towards achieving the SDG targets for maternal health. This study highlights the trends in maternal mortality levels and risk factors in Pakistan between 2007 and 2019. Methods This study compares the results of secondary data analysis of the Pakistan Maternal Mortality Survey 2019 with the Pakistan Demographic and Health Survey 2007. A nested case-control study was carved to compare maternal deaths with the women who survived a pregnancy, in the same sampling clusters during the same period. Logistic regression was used to estimate odds ratios (OR) for major risk factors of maternal mortality after adjusting for the women’s age, parity, education, and wealth quintile. Results In 2019, Pakistan’s MMR was 186 per 100,000 live births, registering a 33% decline from 2007 (rural 42% vs. urban 11%). The leading causes of maternal mortality were postpartum hemorrhage, hypertensive disease of pregnancy, postpartum infection, and post-abortion complications. Women > 35 years and those expecting their first child were more likely to die from childbirth, while those who had ever used family planning had a lower risk according to the data for both years. In 2007, a distance of > 40 kilometers to a hospital significantly increased the risk of mortality but this association was not significant in 2019. In 2019, women who died were more likely to receive antenatal care than those who survived (adjusted OR 9.3); this association was not significant in 2007. Conclusion The modest reduction in MMR can be attributed to improved access to maternal health services in rural areas with increased antenatal care and institutional deliveries. However, most maternal deaths were caused by poor accessibility to quality emergency obstetric care. Lack of family planning remains a major risk factor for high maternal mortality in Pakistan.